2021
DOI: 10.1007/s12529-021-10004-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception, Self-efficacy, Lay Theories of Health, and Engagement in Health-Protective Behaviors Among Hospital Pharmacists During the COVID-19 Pandemic

Abstract: Background Risk perception is an important predictor of health-protective behaviors during pandemics. However, the underlying mechanism connecting risk perception and health-protective behaviors is not well understood. The current study investigates how risk perception predicts hospital pharmacists’ engagement in health-protective behaviors during the peak period of COVID-19 pandemic in China and the mediating effects of lay theories of health and self-efficacy. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…It is worth exploring whether brief interventions on changing people’s implicit theories of health and scalable strategies to enhance self-control among people could improve the effectiveness and efficiency of public health campaigns for promoting healthy living (e.g. Zhang and Kou, 2021; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth exploring whether brief interventions on changing people’s implicit theories of health and scalable strategies to enhance self-control among people could improve the effectiveness and efficiency of public health campaigns for promoting healthy living (e.g. Zhang and Kou, 2021; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Steimer and Mata, 2016), intelligence (e.g. Blackwell et al, 2007), and health (Bunda and Busseri, 2019; Zhang and Kou, 2021; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic, which has led to more than 243 million infections and 4.94 million deaths around the world by October 22nd, 2021, is the most severe public health crisis that human beings are facing since the establishment of the World Health Organization (John Hopkins University, 2020). The high rates of transmission of the COVID-19 virus and the quick spread of misconceptions and rumours about COVID-19 on social media during the early stage of the pandemic induced heightened risk perception -perceived risk of infection during the COVID-19 pandemic -among people around the world (Ioraf et al, 2020;Wise et al, 2020;Zhang et al, 2021). As similar pandemics happened during the past several decades, such as SARS (Maunder et al, 2003;Maunder et al, 2006) and Ebola (Lötsch et al, 2017), the COVID-19 pandemic and the associated containing measures (e.g., social distancing, quarantine) not only posed great challenges to people's physical health but also led to wide-ranging impacts on people's mental health and well-being (Brooks et al, 2020;Qiu et al, 2020;Tan et al, 2020;Tian et al, 2020;Xiang et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Afsar and Masood ( 30 ) found that enhancements in self-efficacy can facilitate innovative work-related behaviors such as PCC. Furthermore, Zhang et al ( 31 ) demonstrated that self-efficacy is positively associated with health protection behaviors among pharmacists during the coronavirus disease 2019 pandemic.…”
Section: Introductionmentioning
confidence: 99%